Perceptions of Indonesian Muslim Youth on Factors Influencing Their Intention to Perform Cash Waqf - Mujahidah, Anisa Syahidah; Rusydiana, Aam Slamet (International Journal of Islamic Economics and Finance (IJIEF), 2023)
This study aims to investigate the intention to donate cash waqf among Indonesian Muslim youth. Additionally, this study explains the theory of planned behavior (TPB) and two additional variables, i.e., Islamic religiosity and willingness. The Partial Least Square Structural Equation Modeling (PLS-SEM) method was employed to evaluate the measurement and structural models. Online questionnaires were then distributed to purposively selected respondents throughout Indonesia, consisting of all major islands. In total, 104 respondents participated. This study uncovered that the attitude and willingness variables affected the intention to donate cash waqf among Indonesian Muslim youth. Meanwhile, subjective norms, perceived behavioral control, and Islamic religiosity variables were not significantly proven as the determinants. With the latest data and variables studied, these findings can be used as guidelines for policymakers, especially waqf regulators and waqf institutions, to innovate and improve the characteristics of cash waqf contributors, primarily among Muslim youth, to maintain the waqf instruments’ sustainability and development.